2008
DOI: 10.1021/ic701700p
|View full text |Cite
|
Sign up to set email alerts
|

Reversible NO Motion in Crystalline [Fe(Porph)(1-MeIm)(NO)] Derivatives

Abstract: The synthesis, characterization, and X-ray structures of three low-spin (nitrosyl)iron(II) tetraarylporphyrinates, [Fe(TpXPP)(NO)(1-MeIm)], where X = F (in a triclinic and a monoclinic form) and OCH 3 are reported. All three molecules, at 100 K, have a single orientation of NO. These structures are the first examples of ordered NO's in [Fe(Porph)(NO)(1-MeIm)] complexes. The three new derivatives have similar structural features including a previously unnoted "bowing" of the N NO -Fe-N Im angle caused by a conc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
49
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 30 publications
(54 citation statements)
references
References 46 publications
5
49
0
Order By: Relevance
“…In form I (Scheme 2, left), 5 neighboring ethyl groups of the macrocycle point to one face of the porphyrin, whereas the remaining 3 point in the opposite direction. In addition to this complication, the bound NO ligand can rotate around the Fe-NO bond, and occupy four basically isoenergetic positions on each side of the porphyrin ring where the oxygen atom of NO is placed between two adjacent nitrogen atoms of the macrocycle 19. Since the two faces of the porphyrin ring are not equivalent, form I can potentially give rise to eight different conformers (A – H) as shown in Figure 1.…”
Section: Results and Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…In form I (Scheme 2, left), 5 neighboring ethyl groups of the macrocycle point to one face of the porphyrin, whereas the remaining 3 point in the opposite direction. In addition to this complication, the bound NO ligand can rotate around the Fe-NO bond, and occupy four basically isoenergetic positions on each side of the porphyrin ring where the oxygen atom of NO is placed between two adjacent nitrogen atoms of the macrocycle 19. Since the two faces of the porphyrin ring are not equivalent, form I can potentially give rise to eight different conformers (A – H) as shown in Figure 1.…”
Section: Results and Analysismentioning
confidence: 99%
“…This is evident from the solid state structures on these compounds which frequently show disorder in the NO orientation (see, for example, ref. 19). Our calculations show that the conformation adopted by the NO ligand relative to the ethyl substituents has a distinct effect on the NRVS data in the region of Fe-porphyrin core vibrations, whereas the electronic structure of the FeNO subunit is hardly affected by changes in the conformation.…”
Section: Introductionmentioning
confidence: 99%
“…Given the interesting ligand dynamics and other issues, we thought that a series of multiple-temperature X-ray studies could provide information on the O 2 ligand rotations, much like those we were able to map out for several six-coordinate nitrosyl iron porphyrinates. 23, 24 In these cases, the lower temperature structures resolved disorder, even though the rotation about the axial Fe–NO bond is a very low barrier process.…”
Section: Introductionmentioning
confidence: 96%
“…This has been further demonstrated in a series of temperature-dependent crystal structures and IR investigation [87]. There are other effects on the structure around iron on the addition of the sixth ligand that have been summarized in references [87][88][89]. We have also characterized additional iron(III) species, espcially six-coordinate species and the original references include the following [90][91][92][93][94].…”
Section: Discussionmentioning
confidence: 72%
“…These complexes showed that the NO stretching frequency is a remote trans bond detecting system [86]. This has been further demonstrated in a series of temperature-dependent crystal structures and IR investigation [87]. There are other effects on the structure around iron on the addition of the sixth ligand that have been summarized in references [87][88][89].…”
Section: Discussionmentioning
confidence: 73%